2020
DOI: 10.1071/rd20098
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription (STAT) 1 and STAT3 are expressed in the human ovary and have Janus kinase 1-independent functions in the COV434 human granulosa cell line

Abstract: Ovarian granulosa cells are fundamental for oocyte maintenance and maturation. Recent studies have demonstrated the importance of members of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling pathway in the granulosa cell population of mouse and horse ovaries, with perturbation of JAK1 signalling in the mouse shown to impair oocyte maintenance and accelerate primordial follicle activation. The presence and role of the JAK/STAT pathway in human granulosa cells has yet to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…Some findings have revealed the involvement of the JAK-STAT pathway in follicular development in mares and mice (47,48). Furthermore, Frost et al confirmed that the JAK-STAT signaling pathway contributes to the crosstalk between oocytes and CCs in humans using the COV434 cell line (49). Another enriched pathway is the TGF-b signaling pathway, which is reported to mediate the activation of primordial follicles, folliculogenesis, and oocyte-CC communication (50).…”
Section: Discussionmentioning
confidence: 98%
“…Some findings have revealed the involvement of the JAK-STAT pathway in follicular development in mares and mice (47,48). Furthermore, Frost et al confirmed that the JAK-STAT signaling pathway contributes to the crosstalk between oocytes and CCs in humans using the COV434 cell line (49). Another enriched pathway is the TGF-b signaling pathway, which is reported to mediate the activation of primordial follicles, folliculogenesis, and oocyte-CC communication (50).…”
Section: Discussionmentioning
confidence: 98%
“…STAT1 and STAT3, which belongs to the signal transducer and activator of transcription (STAT) family, are critical signaling molecules and transcriptional activator that regulate cell growth, survival, and proliferation 23 . STAT1 and STAT3 are expressed in granulosa cells, specifically in the primordial follicles 24 . Emerging evidence has shown that STAT3 prevents follicular atresia and enhances ovarian function in POI animal models 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…23 STAT1 and STAT3 are expressed in granulosa cells, specifically in the primordial follicles. 24 Emerging evidence has shown that STAT3 prevents follicular atresia and enhances ovarian function in POI animal models. 25,26 The mitogen-activated protein kinase (MAPKs), members of the serine/threonine-protein kinase family, are involved in cell proliferation, differentiation, growth, and many other physiological processes.…”
Section: Targetmentioning
confidence: 99%
“…Several studies have demonstrated that the inhibition of the PI3K-AKT pathway leads to apoptosis and autophagy in OGCs [ 60 , 61 ]. The importance of the JAK/STAT signaling pathway in ovarian development and folliculogenesis in horses [ 67 ] and humans [ 68 ] has been demonstrated. Polyfluoroalkyl substances reduce the ovarian reserve and decrease endogenous hormone synthesis by activating the peroxisome proliferator-activated receptor (PPAR) pathway [ 69 ], which has been indicated as a new biomarker of follicular capacity [ 70 ].…”
Section: Discussionmentioning
confidence: 99%